Interference and Level of Economic Damage of Alexandergrass on Corn - FRANDOLOSO,F.S. (2020)
ABSTRACT: The objective of this work was to evaluate the interference and to determine the level of economic damage (NDE) of the weed when infesting the corn crop. Treatments were composed by corn densities (2.60, 3.10, 3.65, 4.00 and 4.80 plants m-1) and 10 Alexandergrass populations for each crop seeding density. The population of plants, leaf area, soil cover and shoot dry mass of Alexandergrass were evaluated as indicator of infestation. Shoot dry mass of Alexandergrass presents better adjustment to the model of rectangular hyperbole, and losses of grain yield due to interference of the weed were satisfactorily estimated by this model. Corn sowing densities of 2.60; 3.10 and 3.65 plants m-1 in average, were more competitive of all evaluated variables in the presence of Alexandergrass. Corn densities of 2.60; 3.10 and 3.65 plants m-1 increase the level of economic damage, justifying the adoption of control measures of Alexandergrass when in higher populations. NDE values ranged from 1.58 to 9.37 plants m-2 at the densities of 4.00 and 4.80 maize plants m-1, which were less competitive with Alexandergrass.